Associations of disordered sleep with body fat distribution, physical activity and diet among overweight middle‐aged men. (2nd February 2015) - Tan, Xiao; Alén, Markku; Cheng, Shu Mei; Mikkola, Tuija M.; Tenhunen, Jarkko; Lyytikäinen, Arja; Wiklund, Petri; Cong, Fengyu; Saarinen, Antti; Tarkka, Ina; Partinen, Markku; Cheng, Sulin
Summary This cross‐sectional study aimed to investigate whether body fat distribution, physical activity levels and dietary intakes are associated with insomnia and/or obstructive sleep apnea among overweight middle‐aged men. Participants were 211 Finnish men aged 30–65 years. Among the 163 overweight or obese participants, 40 had insomnia only, 23 had obstructive sleep apnea only, 24 had comorbid insomnia and obstructive sleep apnea and 76 were without sleep disorder. The remaining 48 participants had normal weight without sleep disorder. Fat mass, levels of physical activity and diet were assessed by dual‐energy X‐ray densitometry, physical activity questionnaire and 3‐day food diary, respectively. Among the overweight participants, we found that: (i) groups with sleep disorders had higher fat mass in trunk and android regions than the group without sleep disorder (P = 0.048–0.004); (ii) the insomnia‐only group showed a lower level of leisure‐time physical activity (436.9 versus 986.5 MET min week−1, P = 0.009) and higher intake of saturated fatty acids (14.8 versus 12.7 E%, P = 0.011) than the group without sleep disorder; and (iii) the comorbid group had a lower level of leisure‐time physical activity (344.4 versus 986.5 MET min week−1, P = 0.007) and lower folate intake (118.9 versus 152.1 μg, P = 0.002) than the group without sleep disorder, which were independent of body mass index. The results suggest that central obesity is associated with insomnia and/or obstructive sleep apnea. In addition, low levels of leisure‐time physical activity and poor dietary intakes are related to insomnia or comorbid insomnia and obstructive sleep apnea among overweight men.